Accurate assessment of alpha‐gal syndrome using cetuximab and bovine thyroglobulin‐specific IgE - Sim, Da Woon; Lee, Jong Sun; Park, Kyung Hee; Jeong, Kyoung Yong; Ye, Young‐Min; Lee, Jae‐Hyun; Park, Jung‐Won (Molecular nutrition & food research, 2017)
Scope IgE against galactose‐α‐1,3‐galactose (α‐Gal) causes alpha‐gal syndrome. Bovine thyroglobulin (BTG) and cetuximab share this epitope. We aimed to determine the utility of specific IgE (sIgE) against cetuximab as compared to BTG for diagnosing alpha‐gal syndrome. Methods and results Twelve patients with alpha‐gal syndrome, 11 patients with immediate beef or pork allergy, 18 asymptomatic individuals with meat sensitization, and 10 non‐atopic subjects were enrolled. We checked the levels of sIgE against BTG and cetuximab using the streptavidin CAP assay. Additionally, IgE reactivity to BTG and cetuximab was assessed by immunoblotting. All alpha‐gal syndrome patients had a high concentration of sIgE against BTG, and cetuximab. In contrast to alpha‐gal syndrome, patients with immediate allergic reactions to meat consumption and those with asymptomatic sensitization had significantly lower concentration of BTG and cetuximab sIgE, and a high prevalence of sIgE against bovine or porcine serum albumin. Although the concentration of sIgE against alpha‐gal was lower in individuals with asymptomatic sensitization, IgE immunoblotting showed the presence of sIgE against α‐Gal in this group. Conclusion Differentiation of alpha‐gal syndrome from patients with immediate allergy to meat consumption or asymptomatic sensitization requires quantification of cetuximab‐ or BTG‐induced sIgE via detection of IgE for α‐gal. This study aims to determine the utility of specific IgE (sIgE) against cetuximab as compared to BTG for diagnosing alpha‐gal syndrome. Patients with alpha‐gal syndrome have significantly higher sIgE concentrations to beef, pork, BTG, and cetuximab than controls. However, these patients showed low sIgE concentrations in response to bovine and porcine serum albumin, similar to those observed in healthy controls. The sIgE against cetuximab and BTG could effectively discriminate between alpha‐gal syndrome and the other three groups.